Mesures de l’efficacité des entreprises artisanales de pêche - Abgrall, Jean-François; Roy, Pauline (L'Actualité économique, 1979)
In this paper, efficiency of artisanal fishing firms is measured using a method elaborated by Yotopoulos and Lau (AER, March 1973). It shows that this method could be used by fishery managers to find new criteria when it comes to decide which fishermen should be granted a license, when entry into the fisheries ought to be limited. The main results may however appear surprising in that they reveal that as a whole fishermen are price efficient, although those more open to new technology have a more business like behavior and tend to be more efficient than the others. Finally those with a larger experience of the labor market outside fisheries reveal a behavior consistant with a perception of the opportunity cost of their labor higher than that shown by those with little experience outside of fisheries.